A longitudinal study of early childhood caries incidence in Wenzhou preschool children - Xiping Wang; Zhiyuan Wei; Qiao Li; Liqin Mei (BMC, 2017)
Abstract Background Early childhood caries (ECC) is a serious public health problem in China. Few studies, however, have described the incidence of ECC in China. The purpose of this study was to assess the prevalence and incidence of ECC among preschool children in Wenzhou China. Methods Preschool children aged 3-4 years old were surveyed and followed up when they reached 5-6 years of age in the city of Wenzhou in southeast China. The rates of dental caries were determined with prevalence, and incidence density for risk of caries of a person (IDp) and of a tooth surface (IDs). Results The prevalence and decayed, missing, and filled primary teeth (dmft) score of 3-4, 4-5, and 5-6 years old children were 59.8% and 2.9, 71.8% and 4.2, and 76.4% and 4.6, respectively. The IDp was 29.7 and 14.8 persons/100 person-year during the first and second year. The IDs was 5.9 and 2.7 newly affected surfaces/100 surface-year, respectively. The percentage of molars with caries experience increased obviously; the percentage of maxillary central incisors and mandibular incisors with caries experience increased during the first follow-up, whereas it declined during the second follow-up; the others increased gradually. Conclusions The prevalence and incidence of dental caries in Wenzhou preschool children were very high with most of the carious teeth left untreated. The molars were the most affected teeth during the observation period.